Fatigue Characteristics and Mechanisms of Additional Damping Structures With Entangled Metallic Wire Material - Tang, Yu; Liang, Jiasong; Wei, Dang; Xiong, Baoquan; Zhu, Zhihui; Wu, Yiwan; Bai, Hongbai (Fatigue & fracture of engineering materials & structures, 2025)
ABSTRACT Under vibration conditions, continuous alternating loads cause fatigue damage to structures, affecting their stability, durability, and overall safety. In this paper, the additional damping structures with entangled metallic wire material (EMWM) is proposed. Dynamic tests with different loading frequencies and loading amplitudes are carried out to evaluate the energy dissipation and stiffness characteristics of the different structures in terms of energy dissipation, loss factor, and average stiffness. Fatigue tests are conducted, and the fatigue life tests are applied with different loading amplitudes and loading frequencies using displacement control, and the fatigue properties are obtained under different numbers of cyclic loading. The test results are analyzed with respect to the energy dissipation mechanism of EMWM and the characteristics of the additional damping structure. The hysteresis curves under different loading times are identified by parameters, and the fatigue mechanical models are constructed. Comparison between the predicted data of the model and the hysteresis curve data of the test indicates that the model has high accuracy.